Efeitos do cádmio e do cobalto no crescimento e em parâmetros bioquímicos e fotossintéticos da clorofícea Raphidocelis subcapitata - Reis, Larissa Luiza dos (Universidade Federal de São Carlos, 2019)
Heavy metals may cause damage to the biota of contaminated environments. The use of multiple endpoints is necessary to better elucidate the mechanisms of toxicity of these compounds. Therefore, this study aimed to evaluate the effects of cadmium (Cd) and cobalt (Co) on growth, biochemical and photosynthetic parameters of the microalgae Raphidocelis subcapitata, through quantification of carbohydrates, lipid composition, concentration of chlorophyll a (Chl a), maximum (ΦM) and effective quantum yields (Φ’M), efficiency of oxygen evolving complex (OEC) and photochemical and non-photochemical quenchings analysis. To date, this is the first study reporting Co effects in lipid classes of a freshwater Chlorophyceae. After 96 hours of exposure, we found an IC50 of 0.58 and 0.85 µM of Cd and Co, respectively. Both metals led to increase of total lipid content and reduction of efficiency of OEC and of ΦM. Chl a was the most efficient endpoint to detect Cd toxicity, after 96 hours of treatment. In relation to Co, cell density and total lipids content were the most sensitive endpoints, since they were altered in all concentrations. The lipid classes most affected by Cd were wax esters – WE (8-fold increase), and triglycerides – TAG (47% reduction), and Co exposure were sterols – ST (4-fold increase), and acetone mobile polar lipid – AMPL (60% reduction). The use of several endpoints enables to detect differences between the mechanisms of action of each metal, as well as the consequences to microalgae. In addition, the cell-level toxicity assessments carried out in this study based on biochemical parameters and photosynthetic efficiency provided faster responses regarding the damage caused by Cd and Co compared to traditional assessments in ecotoxicology, such as cell density measures, specially with regard to interference of Co in the biochemical composition of the microalgae.
Keywords: Ecotoxicologia; Clorofíceas; Metais; Múltiplos endpoints; Ecotoxicology; Chlorophyceae; Metals; Multiple endpoints; CIENCIAS BIOLOGICAS::ECOLOGIA